Kepemimpinan Transformasional: Strategi Kepemimpinan Eko Suwanto Tiga Periode Sebagai Ketua Komisi A DPRD Daerah Istimewa Yogyakarta - Juang Gagah Mardhika (Program Studi Pembangunan Masyarakat Desa (D3), 2025)
This study examines Eko Suwanto's transformational leadership strategy during his three terms as Chair of Commission A of the Yogyakarta Special Region Regional People's Representative Council. Transformational leadership is the main foundation for understanding how Eko Suwanto succeeded in building public trust, establishing effective communication, and inspiring his followers to achieve common goals. This study employs a descriptive qualitative approach using in-depth interviews, observation, and documentation techniques. The findings reveal that Eko Suwanto's success was not solely based on political power but also on innovative strategies he implemented, such as personalised campaign approaches, social media utilisation, and participatory public services. These strategies have strengthened the image of inclusive leadership that is open to change. The impact of his leadership is evident in the improved performance of Commission A, harmonious relations between the government and the community, and increased citizen participation in public decision-making processes. This study recommends that the transformational leadership model applied by Eko Suwanto can serve as an example for other leaders in creating positive change and strengthening democracy at the local level. Thus, this study contributes to the development of leadership science, particularly in the context of public organisations and electoral politics in Indonesia